Author Correction: The pattern-recognition receptor CORE of Solanaceae detects bacterial cold-shock protein. (November 2017) - Wang, Lei; Albert, Markus; Einig, Elias; Fürst, Ursula; Krust, Damaris; Felix, Georg
In the version of this Article originally published, Fig. 6b, which is composed of individual pictures of six plants, inadvertently and erroneously displayed the same image of one Col-0 wt plant twice. This has been corrected so that Fig. 6b now shows two different representative plants for the Col-0 wt control.